Representações sociais sobre a Aids e a Terapia Anti-Retroviral: influências no tratamento de pessoas vivendo com HIV/Aids - CUNHA, Janaina Barbosa Gomes (Universidade Federal do Pará, 2014)
As Antiretroviral therapy evolves, AIDS has acquired chronic disease characteristics especially in those countries in which access to medication is actually guaranteed. Brazil has become a model country since it has a health care program that has presented good results towards epidemic control. In November 1996, the Brazilian National Health Care System announced a law which established the mandatory nature of free access to antiretroviral medicat ion for all those who needed it. The obtained results with treatment – that is, progressive reduction of viral load and maintenance and/or reestablishment of immune system functioning – have been associated to outstanding benefits on physical health of HIV-positive patients which allow these people to resume and materialize their life projects. However, universal access to medication that enables free-of-cost treatment for HIV carriers still faces adherence issues. Considering a more restricted understanding, adherence may be defined as a person’s behavior – such as taking medicine, following guidelines of a diet or adopting changes in life style – that relates to recommendations established by the health care team. In this context, this study proposes to analyzing HIV-positive subjects´ social representations of antiretroviral treatment and its implications on their adherence process to it, therefore featuring images and meanings these HIV-positive individuals who have adhered or not adhered to antiretroviral therapy have about this kind of treatment and its consequences on their lives as well as standing out the objectifications and anchorages that form their social representations. Methodology was based on theoretical formulations about qualitative research, prioritizing interviews focused on Explicitness Method of Underlying Speech. These interviews were held at Parasite and Infectious Diseases Special Reference Unit – this unit belongs to the network of Pará State Health Secretariat health care units – and at João de Barros Barreto University Hospital, more specifically at Parasite and Infectious Diseases Clinical Unit.